HARMONIZATION OF LABOR LAW WITH ILO CONVENTIONS IN LEGAL PROTECTION FOR WORKING CHILDREN - Siti Nurhayati (International Journal of Society and Law, 2025)
Children are a mandate as well as a gift that must be maintained because in them are inherent dignity, dignity, and rights as human beings that must be upheld. Until now, the issue of child labor and child exploitation are two things that are still a serious problem in Indonesia. Indonesia has ratified two ILO conventions related to child labor, namely ILO Convention No. 138 on the Minimum Age for Work and ILO Convention No. 182 on the Prohibition and Immediate Action for the Elimination of the Worst Forms of Child Labor. Law No. 13 of 2013 concerning Manpower in several articles has regulated the existence of working children. In its implementation, the policy of law formation is still inconsistently applied, as evidenced by the still high number of children working in Indonesia. From the description above, the problems to be studied in this paper are: First, how is the form of child labor protection according to the Labor Law number 13 of 2003 related to Law No. 20 of 1999 concerning the ratification of ILO Convention 138 and Law No. 1 of 2000 concerning the ratification of ILO Convention 182? And second, how are the Government's efforts to implement positive laws related to the protection of working children?